Peran Internet di Saat Pandemi Covid-19 Terhadap Kinerja Guru SDN Wonosalam Demak - Nasir, Ahmad; Suryani, Fitri Budi; W, Sri Surachmi (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
The study, entitled the use of the internet during the Covid-19 pandemic on the performance of elementary school teachers in Wonosalam sub-district, Demak district, aims to analyze the effect of internet use on the performance of primary school teachers in Wonosalam sub-district, Demak district. Using ex post facto research methods, with the sampling technique using cluster random sampling with two stage cluster sampling. The data analysis method used is descriptive statistical analysis, and by using a questionnaire to obtain data. The results showed that; 1) In general, it can be described that most of the respondents are familiar and familiar with using information technology facilities; 2) These variations in internet behavior are related to perceptions and understanding of the benefits of the internet which may vary between individuals; 3) Internet use has an influence on performance. The implication of this research can be concluded that to increase the role of the internet in teacher performance during the Covid-19 pandemic is to maximize quality network accessibility, improve IT infrastructure, use friendly and easy to apply (applicable) applications, socialize the use of applications in implementation. Teacher work. For further research, the sample can be reproduced to see patterns of Internet usage by a wider teacher. Future research can also be directed to look at usage patterns based on the life stages of the internet.